DIMENSI PARTISI nGRAF AMALGAMASI BINTANG YANG DIHUBUNGKAN SUATU LINTASAN - Asmiati, Asmiati (MATEMATIKA, 2016)
Let  be a connected graph, vertex , and .  For an ordered k-partition,  the representation v with respect to π is the k-vector ) , are distinct. The minimum k for which there is a resolving k-partition of  is the partition dimension of denoted by  .  In this paper, we determine the partition dimension for certain amalgamation of stars, namely nSk,m.